PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, KUALITAS KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN LABUHANBATU UTARA - Rambe, Amar (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the Influence of Leadership Style, Work Motivation, Quality of Work And Career Development On Employee Performance At the Department of Education Labuhanbatu Utara.  Data collection was conducted through a survey approach with descriptive research type is quantitative, spread questionnaires to 30 respondents (total population), i.e., the employees of the place of research.  The data analysis tool used in this research is using the SPSS (Statistical Product Sofware Solution). The results showed that the partial test (t test) revealed that the Leadership Style has Positive and Significant Effect On Employee Performance At the Department of Education North Labuhanbatu with the value of tcount (3,525) > ttable (1,710) and level of significance 0,002 < 0,05. Work motivation has Positive and Significant with a value of t, namely (3,954) > ttable (1,710) and a significance level of 0,001 < 0,05. Quality of Work have a Positive And Significant with a value of t, namely (4,051) > ttable (1,710) and a significance level of 0,000< 0,05, Career Development Significant Positive Effect with the value of t, namely (4,446) > ttable (1,710) and a significance level of 0,000< 0,05.  Simultaneous (test F) there is a positive and significant influence with Fcount (17,868) > Ftable (2,67) and level of significance 0,00 < 0,05. Through testing the coefficient of determination, the results obtained by 74,1%.  While the rest by 26.1% influenced by other variables not examined in this study.